Peranan Manajemen Humas dalam Membangun Branding Image Di SMP IT Nurul ‘Azizi Medan - Lilis Astika; Syakur Chaniago (Universitas Negeri Malang, 2020)
Abstract: This study aims to examine public relations management strategies in building the branding image of SMP IT Nurul ‘Azizi Medan. Increasing competition among educational institutions requires public relations to play a crucial role in shaping a positive image and enhancing the school’s appeal to the public. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. The findings indicate that public relations activities have been implemented actively through social media, community-based programs, and intensive communication with parents. Supporting factors include strong leadership support, active participation from teachers and students, and a high level of public trust. However, challenges remain, particularly in terms of limited human resources, insufficient promotional budgets, and low digital literacy. Strengthening public relations planning and implementing more professional management are essential steps to enhance the school’s branding strategy. Keywords: public relations management, branding image, school Abstrak: Penelitian ini bertujuan untuk mengkaji strategi manajemen humas dalam membangun branding image di SMP IT Nurul ‘Azizi Medan. Persaingan yang semakin ketat antar lembaga pendidikan menuntut peran humas untuk menciptakan citra positif dan meningkatkan daya saing sekolah di mata publik. Pendekatan yang digunakan adalah kualitatif deskriptif, dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan studi dokumen. Hasil penelitian menunjukkan bahwa aktivitas humas telah berjalan secara aktif melalui media sosial, kegiatan eksternal, serta komunikasi intensif antara sekolah dan orang tua. Faktor pendukung keberhasilan mencakup dukungan pimpinan sekolah, partisipasi guru dan siswa, serta kepercayaan masyarakat yang kuat. Sementara itu kendala yang dihadapi meliputi keterbatasan sumber daya manusia, minimnya anggaran promosi, dan rendahnya literasi digital. Peran strategis humas dalam membentuk citra institusi perlu diperkuat melalui perencanaan yang sistematis dan pengelolaan profesional. Kata Kunci: manajemen hubungan masyarakat, branding image, sekolah